2020
DOI: 10.3390/electronics9040695
|View full text |Cite
|
Sign up to set email alerts
|

A Novel FastSLAM Framework Based on 2D Lidar for Autonomous Mobile Robot

Abstract: The autonomous navigation and environment exploration of mobile robots are carried out on the premise of the ability of environment sensing. Simultaneous localisation and mapping (SLAM) is the key algorithm in perceiving and mapping an environment in real time. FastSLAM has played an increasingly significant role in the SLAM problem. In order to enhance the performance of FastSLAM, a novel framework called IFastSLAM is proposed, based on particle swarm optimisation (PSO). In this framework, an adaptive resampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…The authors of [18] investigated the performance of Gmapping and Cartographer for autonomous vehicles. In [22], the authors proposed a Fast-SLAM which has a similar foundation as Gmapping since both use Rao-Blackwellised particle filter [13]. Both [18] and [22] concluded that their approach produced satisfactory results but only with the help of IMU and very reliable wheel odometry data.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [18] investigated the performance of Gmapping and Cartographer for autonomous vehicles. In [22], the authors proposed a Fast-SLAM which has a similar foundation as Gmapping since both use Rao-Blackwellised particle filter [13]. Both [18] and [22] concluded that their approach produced satisfactory results but only with the help of IMU and very reliable wheel odometry data.…”
Section: Related Workmentioning
confidence: 99%
“…In [22], the authors proposed a Fast-SLAM which has a similar foundation as Gmapping since both use Rao-Blackwellised particle filter [13]. Both [18] and [22] concluded that their approach produced satisfactory results but only with the help of IMU and very reliable wheel odometry data. Authors of [23] described a dual LiDAR system paired with IMU and wheel odometry to achieve mapping accuracy of up to 4cm.…”
Section: Related Workmentioning
confidence: 99%
“…Zhang and collaborators, by comparing three SLAM algorithms and integrating a path planning analysis to assess their applicability in indoor rescue environments, have provided guidance for researchers in the construction of SLAM systems [ 29 ]. Lei improved the FastSLAM algorithm framework by introducing virtual particles as a global optimization objective and utilizing a particle swarm optimization approach [ 30 ]. Mu and colleagues proposed a graph-based multi-sensor SLAM (Simultaneous Localization and Mapping) method.…”
Section: Introductionmentioning
confidence: 99%
“…Fast SLAM breaks down a SLAM problem into a robot positioning problem and a set of landmark estimation problems that are conditional on the robot status estimation [7]. So far, advanced versions of Fast SLAM have been offered by Lei et al [8], but all of them are based on one basic rule; as reported by Murphy [9], the representation as such is accurate due to the natural conditional independence in the SLAM problem. Fast SLAM uses a modified particle filter to estimate the posterior paths of the robot.…”
Section: Introductionmentioning
confidence: 99%